Abandoning distinctiveness: The influence of nostalgia on consumer choice. Issue 10 (28th May 2020) - Fan, Yafeng; Jiang, Jing; Hu, Zuohao
Abstract: This study proposes that when feeling nostalgic, consumers are more likely to choose the option that the majority of others prefer. Four studies consistently demonstrate that nostalgia can enhance consumers' social connectedness, which motivates them to maintain the feelings of connection to the group and thereby increases their preference for majority‐endorsed options in the subsequent product choices. Moreover, the strength of social ties between consumers and others moderates the mediation effect of social connectedness. In the weak social ties condition, social connectedness mediates the effect of nostalgia on preference for majority‐endorsed products. In the strong social ties condition, the mediation effect of social connectedness diminishes. These findings complement previous work on how nostalgia influences consumer behavior.